Zapisz krócej podaną sumę:

a) 2a + 3b - c - 4a - 3b + 2c=..................................
b) 3x - 2y + 3,5x - y + 2 + o,5y=...............................
c) xy + 3x - y + 1 - 2xy - 2x + y + 1=...........................
d)x² + 2xy - 3y₂ - 2x² - y² - x² + 2xy=.........................
e) ⅙t² + ⅓k²t + ⅓tk² - k²t + ½t² - ⅙tk²=....................
f) u²v² + ¼uv - 1/7u²v² - uv - ½uv + u²v²=..................

3

Odpowiedzi

Najlepsza Odpowiedź!
2010-02-01T16:25:48+01:00
A) 2a + 3b - c - 4a - 3b + 2c=-2a+c
b) 3x - 2y + 3,5x - y + 2 + o,5y=6,5x-2,5y+2
c) xy + 3x - y + 1 - 2xy - 2x + y + 1=x-xy+2
d)x² + 2xy - 3y₂ - 2x² - y² - x² + 2xy=-2x^2-4y^2+4xy
e) ⅙t² + ⅓k²t + ⅓tk² - k²t + ½t² - ⅙tk²=(2/12+6/12)t^2-2/3k^2t+(2/6-1/6)tk^2=8/12t^2-2/3k^2t+1/6tk^2=2/3t^2-2/3k^2t+1/6tk^2
f) u²v² + ¼uv - 1/7u²v² - uv - ½uv + u²v²=1 6/7u^2v^2-1 1/4uv
2 3 2
2010-02-01T16:30:16+01:00
A) -2a +c
b) 0,5x -2,5y +2
c) -xy +x
d) -2x² +4xy -4y²
e) 2/3t² -2/3k²t -⅙tk²
f)1i6/7u²v² -1i1/4uv
1 1 1
2010-02-01T16:34:44+01:00
A) 2a + 3b - c - 4a - 3b + 2c= -2a+c
b) 3x - 2y + 3,5x - y + 2 + o,5y= 6,5x-2,5y+2
c) xy + 3x - y + 1 - 2xy - 2x + y + 1= -xy+x+2
d)x² + 2xy - 3y₂ - 2x² - y² - x² + 2xy= - 2x²+4xy-4y²
e) ⅙t² + ⅓k²t + ⅓tk² - k²t + ½t² - ⅙tk²= ⅔t²-⅔k²t+⅙tk²
f) u²v² + ¼uv - 1/7u²v² - uv - ½uv + u²v²= 1 ⁶/₇ u²v²- 1¼uv